NOTCH Signaling in Aortic Valve Development and Calcific Aortic Valve Disease - Wang, Yidong; Fang, Yuan; Lu, Pengfei; Wu, Bingruo; Zhou, Bin (Frontiers in Cardiovascular Medicine, 2021)
NOTCH intercellular signaling mediates the communications between adjacent cells involving in multiple biological processes essential for tissue morphogenesis and homeostasis. The NOTCH1 mutations are the first identified human genetic variants that cause congenital bicuspid aortic valve (BAV) and calcific aortic valve disease (CAVD). Genetic variants affecting other genes in the NOTCH signaling pathway may also contribute to the development of BAV and the pathogenesis of CAVD. While CAVD occurs commonly in the elderly population with tri-leaflet aortic valve, patients with BAV have a high risk of developing CAVD at a young age. This observation indicates an important role of NOTCH signaling in the postnatal homeostasis of the aortic valve, in addition to its prenatal functions during aortic valve development. Over the last decade, animal studies, especially with the mouse models, have revealed detailed information in the developmental etiology of congenital aortic valve defects. In this review, we will discuss the molecular and cellular aspects of aortic valve development and examine the embryonic pathogenesis of BAV. We will focus our discussions on the NOTCH signaling during the endocardial to mesenchymal transformation (EMT) and the post-EMT remodeling of the aortic valve. We will further examine the involvement of the NOTCH mutations in the postnatal development of CAVD. We will emphasize the deleterious impact of the embryonic valve defects on the homeostatic mechanisms of the adult aortic valve for a purpose of identifying the potential therapeutic targets for the disease intervention.